A COMPARATİVE ANALYSİS OF NARRATİVES ON THE DESTRUCTİON OF BAGHDAD DURİNG THE MONGOL INVASİON - Yilmaz, Metin (Al-Adab Journal, 2024)
Certain historical events have profound and lasting traumatic effects on societies, with their consequences never truly erased from collective memory. The invasion of Baghdad by the Mongols is undeniably one such significant historical event. The importance of Baghdad as the capital of the caliphate, coupled with its role as the religious administrative center for the entire Islamic region in the Middle Ages, further heightened the traumatic impact of this invasion. Indeed, even during the modern-day occupation of Iraq, there was a felt need to reference and compare it to the Mongol invasion. In this study, we will delve into the material destruction caused by the Mongol armies in Baghdad based entirely on historical narratives. We will attempt to scientifically present the value of diverse historical sources by employing historical arbitration methodologies. Specifically, the extent of the destruction inflicted upon the selected sample of Baghdad libraries will be determined through primary sources. The backbone of our study will be the accounts of eyewitnesses who directly experienced the invasion, along with the narratives provided by significant scholars and travelers describing post-invasion Baghdad. Examples of information and methodological errors that modern sources have fallen into with their one-sided narratives will be provided. Sharing the historical realities hidden between the lines with the scholarly community is our primary goal, rather than engaging in the exaggeration and populism that often characterize discussions of this historically renowned event, which holds within it many foundational assumptions.